Hatim tai kay qisay - Hasan sibte (Ferozesons; Lahore, 2002)
"Hatim Tai Kay qisay highlights the legendary acts of generosity, courage, and wisdom of Hatim Tai, depicting his selfless nature and moral integrity as an epitome of true leadership and humanity in Arab folklore.